The Relationship between Gymball use and the Duration of Active Phase 1 in Primigravida Mothers - Rahmi Padlilah; Ika Yulianti; Doris Noviani; Ayu Hari Setiawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Prolonged labour can cause death, infection, exhaustion, ehydration, and postpartum hemorrhage. In a long fetus, there is a risk of causing infection, injury and asphyxia which can increase infant mortality. prolonged labour can be prevented by doing complementary care, relaxation techniques that relieve prolonged labour and provide healthy childbirth outcomes, yoga, pregnancy exercises and gymball techniques. The purpose of this study is to analyze the effectiveness of gym ball on the duration of 1 active phase of primigravida labor. This type of quasy experimental research was conducted at Pertamina Hospital, Tarakan City, from April to June 2024. The sample in this study was 20 respondents using purposive sampling. The interventions given were gym balls on pelvic rocking movement patterns, rebozo, and child's pose techniques. Bivariate analysis using the chi square test. Multivariate analysis in the form of multiple logistic regression. The results of bivariate analysis showed that there was a significant relationship between the gym ball group and the duration of 1 active phase. This is shown by a p value of 0.020 <0.05.